Public Knowledge Improvement of the Medicinal Plant as Immunomodulator in Pandemic Era - Hidayati, Nur Rahmah; Nisa, Ikrima Khaerun; Nisa, Fitrotun; Nurunnisa, Syafira Indah; Bakti, Riska Disa Alussa (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2022)
Vaccination is an effort to prevent Covid-19. In addition, the 5M health protocols, such as wearing masks, washing hands, maintaining distance, avoiding crowds, and reducing mobility are not enough to avoid Covid-19. Education is needed as an effort to increase public knowledge about the use of medicinal plants during a pandemic. The method that used in this study includes a preparation, implementation, and reports. Pretest and posttest values were analyzed by univariate and bivariate. The results showed that there was a change in the level of knowledge, such as a decrease in low-knowledge category from 11.6% to 2.3%, the middle-knowledge category from 48.8% to 11.6% and an increase in good-knowledge category from 39.5% to 86.0 %. Wilcoxon test used in this study with 95% confidence level showed that there was a significant difference between before and after education (p value = 0.000). The education is able to increase public knowledge, especially Muhammadiyah society about the use of medicinal plants to increase immunity during a pandemic.